أثر العامل النحوي في إنكار الحكم النحوي - نبراس عبد الكاظم ثاني تالي, الباحث; رياض عبود أهوين, أ . د. (لارك للفلسفة واللسانيات والعلوم الاجتماعية, 2026)
المُلخّص:يسعى البحث الوقوف على الأثر الذي يجلبه العامل لإصدار حكم الإنكار في النحو العربي، فيتضمن ما أنكره النحويون من تراكيب نحوية، ولا سيما في التراث النحوي العربي، فرفضوا تلك التراكيب التي عدَّها النحويون خروجًا عن الأسس التي وضعت من قبلهم بناءً على نظرية العامل في النحو العربي، فكان اصدار حكم الإنكار قائم على أدلة وعلل توصل إليها النحوي عن طريق العامل، ولا بد من الإشارة إلى ارتباط فكرة العمل بالمتكلم نفسه سواء بالرفع أو بالنصب أو بالجر أو بالجزم(الموصلي: 1/ 111). لذلك فالعامل: "هو ما عمل في غيره شيئًا من رفع أو نصب أو جر أو جزم على حسب اختلاف العوامل"(ابن بابشاذ، 1978م: 2/ 294). وقد تناول البحث مفهوم الإنكار لغة واصطلاحًا، وبعدها جلى عن جملة من الأمثلة التي تبين أثر العامل النحوي في توظيف حكم الإنكار، وقد وازن البحث بين آراء المنكر على رأي معين، وناقل الإنكار، ثم ترجيح ما ثبت بالبحث والتقصي صوابه، وخُتِم البحث بجملة من النتائج التي توصل إليها الباحث.AbstractThe present study aims to explore the impact of the agent in eliciting judgments of negation within Arabic grammar. It examines the grammatical structures rejected by grammarians, particularly within the classical Arabic heritage, who dismissed such constructions as deviations from the established foundations of Agency Theory.The issuance of a negation ruling was predicated on evidence and linguistic justifications derived by grammarians through the Agent Mechanism. It is essential to note that the concept of action is intrinsically linked to the speaker's articulation of the nominative, accusative, genitive, or jussive cases (Al-Mosuli, ). Thus, the Agent is defined as that which effects a change in another, be it nominative, accusative, genitive, or jussive, varying according to the specific nature of the Agents (Ibn Babshadh, 1978).The study explores the concept of negation from both linguistic and terminological perspectives. It subsequently elucidates a series of examples demonstrating the Agent's role in employing the judgment of negation. Furthermore, the study balances the views of those who negate a specific opinion against those who transmit such negations, ultimately weighing the evidence to favor what is proven correct through rigorous investigation. The study is concluded with a summary of the key findings.
Keywords: العامل، الإنكار، النحو، الأثر، رفض الحكم.